CE with chemiluminescence detection for the determination of thyroxine in human serum. Issue 7 (27th December 2013) - Mu, Xiaomei; Li, Shuting; Lu, Xin; Zhao, Shulin; Phillips, Terry M.
<x xml:space="preserve">Abstract</x> A sensitive and rapid approach to perform thyroxine (T4) assay by CE with chemiluminescence (CL) detection was developed. The sensitive detection was based on the enhancement effect of T4 on the CL reaction between luminol and potassium permanganate (KMnO4) in alkaline solution. A laboratory‐built reaction flow cell and a photon counter were deployed for the CL detection. Experimental conditions for CL detection were studied in detail to achieve maximum assay sensitivity. Optimal conditions were found to be 5.0 × 10−4 M luminol added to the CE running buffer and 9.2 × 10−5 M KMnO4 in 0.072 M NaOH solution introduced postcolumn. In the optimized experimental conditions, the linear range for T4 detection was 6.0 × 10−8–6.0 × 10−6 M, with the detection limit of 2.0 × 10−8 M (S/N = 3). Six human serum samples from healthy subjects, hyperthyroid patients and hypothyroid patients were analyzed by the presented method. The serum level of T4 in healthy subjects was found be 9.0 × 10−8 M, whereas the T4 level was found to be 15.6 × 10−8 M in hyperthyroid patients and 1.3 × 10−8 M in hypothyroid patients. The results suggested a potential application of the proposed assay in rapid primary diagnosis of diseases such as hyperthyroid and hypothyroid.